Naše pravo in pravo ljudstvo - Avbelj, Matej (Podjetje in delo, 2016)
The article focuses on the impact of populism on the Slovenian constitutional order and, in particular, on how the latter can defend itself against populism. The argument consists of three parts. In the introduction the main concepts: populism and constitutional democracy are laid out. This is followed by a brief analysis of the populist practices in the Slovenian political and legal life. The article concludes by stipulating several normative proposals to strengthen the Slovenian constitutional democracy against the encroachments of populism.
Keywords: demokracija; populizem; Slovenija; ustava; ustavno pravo